Non-pharmacological interventions for pain in people with dementia: A systematic review. (December 2021) - Liao, Yo-Jen; Parajuli, Jyotsana; Jao, Ying-Ling; Kitko, Lisa; Berish, Diane
Abstract: Context: Pain commonly occurs in people living with dementia but is often undertreated. Non-pharmacological interventions are a safer first-line option for pain management, but evidence-based interventions for people living with dementia have not been established. An increasing number of studies have examined the effect of non-pharmacological interventions in pain management. However, the evidence that specifically focuses on people living with dementia has not been systematically reviewed. Objectives: This review aimed to systematically synthesize current evidence on non-pharmacological interventions to manage pain in people living with dementia. Methods: A comprehensive search of the literature was conducted in PubMed, CINAHL, Scopus, and Web of Science databases. Studies were included if they were 1) peer-reviewed original quantitative research, 2) tested the effect of non-pharmacological interventions on pain in people with dementia, and 3) English language. Studies were excluded if they 1) included both pharmacological and non-pharmacological interventions and did not report separate results for the non-pharmacological interventions; 2) enrolled participants with and without dementia and did not have separate results reported for individuals with dementia; 3) tested dietary supplements as the intervention; and 4) were not original research, such as reviews, editorials, commentaries, or case studies. Title, abstract, and full text were screened. Quality assessment was conducted using the Cochrane Risk of Bias tool and Johns Hopkins Level of Evidence. Pain assessment tools, participant characteristics, study designs, intervention condition, and results were extracted. Results were synthesized through grouping the type of the interventions and weighting evidence based on quality and design of the studies. Results: A total of 11 articles and 12 interventions were identified. A total of 486 participants were included. Interventions that have shown a positive impact on pain include ear acupressure, music therapy, reflexology, tailored pain intervention, painting and singing, personal assistive robot, cognitive-behavioral therapy, play activity, and person-centered environment program. Nevertheless, a majority of the interventions were only evaluated once. Moreover, most studies had similar sample characteristics and setting. Conclusion: Overall, the quality of included studies were mostly low to mixed quality and most participants only had mild to moderate baseline pain, which limits detection of the intervention's effect. Hence, these findings need to be duplicated in studies with a greater sample size, a more diverse population (race, gender, and settings), and a more rigorous design to validate the results.